Unmasking Currents: Thinking Power and War with Foucault and the Black Panthers - Jason Demers (Transatlantica)
This article explores the relationship between Michel Foucault and the Black Panther Party (BPP). It considers precise points of intersection in late 1968 and 1971, when Foucault was reading BPP texts, and when the Groupe d’information sur les prisons (GIP) produced a booklet on the assassination of renowned political prisoner and BPP member George Jackson. Rather than pursuing claims about causal-chronological influence, the article teases out undercurrents—Nietzsche, Mao, Clausewitz, and revolutionary activist projects—that act as sites of confluence with respect to power and war. It is in the face of the violent state suppression of revolt on either side of the Atlantic that Foucault turns to war as an analytic for civil relations in his lectures at the Collège de France. In the context of such a war, assassination, trial, detention, and other strategic political operations are masked as juridical procedures.